Pengembangan website sistem informasi Desa Sibagindar Kecamatan Pagindar Kabupaten Pakpak Bharat menuju desa digital - Waluyo, Bakti Dwi; Karo Karo, Ichwanul Muslim; Harliana, Putri (TEKMULOGI: Jurnal Pengabdian Masyarakat, 2024)
The digital village is a government program that aims to minimize the information gap in rural areas through the use of information and communication technology, and is mandated by Law No. 6/2014. There are four important aspects of a digital village: village governance, economy and food security, village community empowerment, and support facilities. Sibagindar Village, Pagindar Subdistrict, Pakpak Bharat Regency, North Sumatra, is a village that is still an independent, underdeveloped and non-digital village. The village has only one aspect (supporting equipment aspect) of the four aspects that support a digital village. To accommodate the other three aspects so that they are integrated with each other, a platform is needed that can unite them. The information system website can be an integration platform for all aspects that will be digitized later. In addition, the information system website is also a digital gateway to Sibagindar Village. Thus, this activity focuses on the development of an information system website. The stages for the realization of the program include identification of conditions, collection of user requirements, system design, system development, and support for the management of the information system website. The appearance of the website is appropriate and very much in accordance with the results of user requirements gathering. Accessibility of the website is very easy for any device. As much as 83% of the village government and the village community recognized that the presence of the Sibagindar Village Information System website is very useful and motivated to disseminate it.